Gambaran Pengetahuan Ibu dan Praktik Pemberian Makan Pada Anak Usia 12-24 Bulan Dengan Malnutrisi di Kecamatan Selemadeg Kabupaten Tabanan Tahun 2022 - Luh Ayu Adnyani; Gusti Ayu Marhaeni; Made Widhi Gunapria Darmapatni (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2023)
The increasing number of case of malnutrition in Selemadeg District shows that nutritional problem are still a public health problem. The incidence of malnutrition occurs due to ignorance and/or inability to prepare complementary food that can provide the needs of balanced and hygienic nutrition. The purpose of this study was to identify how the description of mother knowledge and feeding practices among children aged 12-24 months with malnutrition in Selemadeg District. This research is a descriptive research with cross-sectional approach. The population of this study were all mother who had children aged 12-24 months in Selemadeg District. The sampling technique is non probability sampling namely total sampling with total sampel 63 responden. The study found that the level of knowledge of responden in a good category was 90,47 %, most of practice levels (60,3 %) were in medium category and 54 % of respondens with a good knowledge have medium level of practice. Suggestion for health worker to organize councelling and demonstration of feeding practices esspesially about how to serve the foodsKeywords : Knowledges, child feeding practices, children aged 12-24 months, malnutrition.